Synthesis method and application of wheat ear-shaped nickel-doped ZSM-22 zeolite assembled by nanoparticles
By using 1,6-hexanediamine and nickel acetylacetonate during the synthesis of ZSM-22 zeolites, the nucleus formation and grain growth were controlled, and the problems of ZSM-22 zeolites are easily deactivated and pore structure discomfort in the catalytic reaction were solved, and metal nickel-doped ZSM-22 zeolite with wheat ear morphology and high catalytic activity were synthesized.
Patent Information
- Application Number
- CN202310189798.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-03-02
AI Technical Summary
The existing ZSM-22 zeolites are prone to cracking in catalytic reactions and the catalysts are prone to deactivate. In traditional methods, when synthesizing porous ZSM-22 zeolites, polymers are required as soft template agents, making it difficult for aluminum species to enter the zeolite skeleton, reduce acid amount and crystallinity.
1,6-hexanediamine was used as the structural template agent, and nickel acetylacetonate was added during the hydrothermal process to control the water content and 1,6-hexanediamine content in the gel to form a large number of crystal nuclei, inhibit the growth of ZSM-22 zeolite grains and introduce defects, and synthesize metal nickel-doped ZSM-22 zeolite with wheat ear morphology.
The successful synthesis of ZSM-22 zeolite nanobuoys with high surface area and more available acid sites exposed, significantly improving catalytic activity, especially in the hexadecanoic acid hydrodeoxygenation reaction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0004105024900000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zeolite molecular sieve synthesis, and in particular relates to a method for synthesizing a metal nickel-doped ZSM-22 zeolite which contains abundant gaps, is assembled by nanoparticles and has a wheat-ear-shaped morphology. Background Art
[0002] In the 1980s, Mobile Corporation of the United States successfully developed ZSM-22 zeolite molecular sieve, which is a microporous material with a TON topological structure. It is composed of a five-membered ring, a six-membered ring and a ten-membered ring, forming a structural feature with a one-dimensional open ten-membered ring straight channel. Due to its special pore structure characteristics and adjustable acid properties, it shows excellent catalytic performance in hydrogenation isomerization, methanol to olefins, aromatic alkylation, and xylene isomerization reactions. However, due to the pore structure characteristics of ZSM-22 zeolite itself, it only has a microporous structure, which is not conducive to the diffusion of reaction molecules, resulting in its easy cracking during the reaction and the catalyst is easy to deactivate. To solve this problem, a mesoporous structure is introduced during the synthesis of ZSM-22 zeolite or ZSM-22 zeolites of different morphologies are synthesized to improve the diffusion of molecules, reduce its cracking performance, and increase the stability of the catalyst.
[0003] In recent years, researchers have done a lot of research work around the synthesis of porous ZSM-22 zeolite. For example, MCM-41 was introduced into the synthesis process of ZSM-22 zeolite to successfully prepare MCM-41@ZSM-22 composite catalytic materials. In addition, structural defects were introduced into the zeolite framework by combining traditional acid-base treatment. The above method can introduce mesoporous structure on the surface of ZSM-22 zeolite, which can improve the diffusion effect of reaction molecules and improve its catalytic activity to a certain extent. However, the synthesis process is relatively complicated, and the synthesis ratio requirements are strict, or a large amount of wastewater is generated during the post-treatment process, causing environmental pollution, which limits its further scale-up synthesis. The soft template method is also a commonly used method for synthesizing porous ZSM-22 zeolite, such as: Patent (CN108529647B) reports a method for synthesizing mesoporous ZSM-22 zeolite, that is, a polymer needs to be introduced as a mesoporous template agent during the synthesis process. After high-temperature calcination, the mesoporous template agent dispersed inside the zeolite particles is removed, and a rich mesoporous structure is generated inside the ZSM-22 zeolite particles, which effectively improves the diffusion effect of molecules. It requires a polymer containing a quaternary ammonium group as a soft template agent to produce defects in the zeolite grains and produce mesopores. However, these methods require additional polymers to be added, which not only makes it difficult for aluminum species to enter the zeolite framework during the zeolite crystallization process, resulting in an increase in the zeolite silicon-aluminum ratio and a decrease in the acid content, but also reduces the zeolite crystallinity. If a polymer soft template agent is not used, and only a small molecule template agent such as 1,6-hexanediamine is used, the final results show that the BET specific surface area, mesoporous pore volume, and external surface area of the obtained zeolite are all reduced, and the catalytic activity is significantly reduced.
[0004] How to prepare ZSM-22 zeolite with high acid content and micropores and mesopores by using only 1,6-hexanediamine as a template without adding soft templates such as high molecular weight polymers, so that it can expose more available acid sites and have excellent catalytic performance, requires further research. Summary of the invention
[0005] The present invention provides a method for synthesizing a novel ZSM-22 zeolite with wheat-ear-shaped morphology containing metallic nickel. In the present invention, 1,6-hexanediamine is used as a structural template, and nickel acetylacetonate is added during the synthesis process. During the hydrothermal process, the water content in the gel process is reduced, the content of 1,6-hexanediamine is increased, the initial gel becomes saturated, and the conditions for forming a large number of crystal nuclei are provided. A large number of crystal nuclei are formed, which effectively inhibits Ostwald ripening, inhibits the growth of ZSM-22 zeolite grains to a certain extent, and introduces defects at the same time; on the other hand, the zeolite small grains grow axially along the Z-axis, and successfully synthesizes ZSM-22 zeolite nanobeams (ZSM-22-S) with a high external surface area, more available acid sites exposed, and containing metallic nickel and having a wheat-ear-shaped morphology.
[0006] The specific implementation steps of the present invention are as follows:
[0007] Synthesis of a wheat ear-shaped nickel-doped ZSM-22 zeolite:
[0008] Potassium hydroxide solution is added to aluminum sulfate solution to obtain solution A; then 1,6-hexanediamine (DHA) structure directing agent is added to distilled water, and after it is completely dissolved, nickel acetylacetonate is added and stirred to clarify to obtain solution B; solution B is slowly added dropwise to solution A, and the system becomes viscous, and finally silica sol is added, stirred vigorously to form silica-alumina gel, and finally loaded into a kettle for high-temperature static crystallization. After the crystallization is completed, after washing, filtering, drying and high-temperature calcination, a nickel-doped wheat ear morphology ZSM-22 zeolite is obtained, which is marked as ZSM-22-S.
[0009] The ratio of each component of the silica-alumina gel formed above is Al2O3:5-15K2O:2500-3500H2O:100-140SiO2:0.02-3Ni 2+ :45~70DHA, preferably Al2O3:5~10K2O:2500~3000H2O:100~130SiO2:0.38~2.3Ni 2+ :45~65DHA. Further, the molar ratio of H2O:DHA is in the range of 42~67.
[0010] Furthermore, the crystallization temperature is 140 to 180° C., and the crystallization time is 12 to 48 hours.
[0011] Nickel-doped wheat-ear-shaped ZSM-22 zeolite shows excellent activity in the hydrodeoxygenation of hexadecanoic acid.
[0012] Further, the conditions for preparing hexadecane by hydrodeoxygenation of hexadecanoic acid are:
[0013] The hydrodeoxygenation reaction of hexadecanoic acid was carried out in a parr kettle. The catalyst was reduced before the reaction. The reduction procedure was as follows: the catalyst was raised from room temperature to 550°C at 2°C / min and maintained for 2h, with a H2 flow rate of 100mL / min. After cooling to room temperature, the reduced catalyst was poured into a reactor containing a reaction liquid in a hydrogen atmosphere. The reaction conditions were: reaction temperature 260°C, reaction pressure 4.0MPa, reaction speed 500rmp, and reaction time 4h; the reaction liquid was a hexadecanoic acid solution with a concentration of 5g / L, the reaction liquid solvent was decahydronaphthalene, the amount of catalyst in the reaction liquid was 5g / L, and the reaction liquid after the reaction was analyzed by gas chromatography.
[0014] Compared with the prior art, ZSM-22-S zeolite has the following advantages:
[0015] (1) The present invention does not use a high molecular weight polymer as a soft template agent, but uses 1,6-hexanediamine as a small molecule template agent. By controlling other reaction conditions, a wheat-ear-shaped ZSM-22 zeolite containing both intracrystalline mesopores and stacked pores is synthesized only under static crystallization conditions; in addition to providing a nickel active component, nickel acetylacetonate in the present invention also interacts with 1,6-hexanediamine, so that during the nucleation and growth of the zeolite, the nickel acetylacetonate molecules are close to 1,6-hexanediamine, which not only inhibits the accumulation of metallic nickel and improves the dispersion of metallic nickel, but also affects the induced nucleation of 1,6-hexanediamine, so that during the nucleation and growth of the zeolite, the morphology of the zeolite is changed to a certain extent.
[0016] (2) The present invention uses a high concentration of 1,6-hexanediamine to reduce the water content in the gel system, inhibiting the growth of ZSM-22 zeolite grains to a certain extent, so that the small zeolite grains grow along a certain direction. Compared with the existing traditional needle-shaped ZSM-22 zeolite, the ZSM-22-S zeolite has a wheat ear shape, that is, one end of the nanorod is formed by the accumulation of finer nanofiber bundles, and the diameter of the nanofiber bundle is 50-70nm, while the diameter of the nanorod of the traditional needle-shaped ZSM-22 is 500-600nm. These differences in morphology result in ZSM-22-S zeolite having more suitable acidity;
[0017] (3) The synthesized ZSM-22-S zeolite increases the interaction between the metal nickel and the carrier, so that many nickel species are dispersed on the outer surface of the zeolite nanofiber bundles, increasing the utilization rate of the metal nickel. Its activity in the hydrodeoxygenation reaction of hexadecanoic acid is significantly higher than that of the traditional ZSM-22 zeolite-supported nickel and the traditional ZSM-22 zeolite-doped nickel catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the X-ray powder diffraction pattern of Example 1.
[0019] Figure 2 This is a scanning electron microscope photograph of Example 1.
[0020] Figure 3 This is a transmission electron microscope photograph of Example 1.
[0021] Figure 4 It is the N2- adsorption isotherm diagram and pore size distribution curve diagram of Example 1.
[0022] Figure 5 This is a scanning electron microscope photograph of Comparative Example 1.
[0023] Figure 6 It is the X-ray powder diffraction pattern of comparative example 2.
[0024] Figure 7 It is the X-ray powder diffraction pattern of comparative example 3.
[0025] Figure 8 This is a scanning electron microscope photograph of Comparative Example 3.
[0026] Fig. 9 This is a scanning electron microscope photograph of Comparative Example 4. DETAILED DESCRIPTION
[0027] In order to further understand the purpose, content and advantages of the present invention, the specific implementation scheme of the present invention is described in detail as follows, but it is not limited to the following examples, and it should be freely matched according to actual conditions. The composition of silica sol: 70wt.% H2O and 30wt.% SiO2.
[0028] Embodiment 1:
[0029] 0.56g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 7.0g 1,6-hexanediamine structure directing agent was added to 20.6g distilled water, and after it was completely dissolved, 0.6g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, the system became viscous, and finally 20.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3:5K2O:2500H2O:100SiO2:2.3Ni 2+ :60DHA. Finally, the kettle was loaded for high-temperature static crystallization at a temperature of 160°C for 48 hours. After the crystallization was completed, after washing, filtering, drying and high-temperature calcination, a wheat ear-shaped nickel-doped ZSM-22 zeolite was obtained. The framework silicon-aluminum (Si / Al) ratio of the zeolite is 40, the theoretical loading of Ni in the zeolite is 2.1%, and the actual mass fraction is 1% (the actual loading of nickel is obtained based on the characterization of the catalyst by X-ray fluorescence spectroscopy or atomic emission spectrometer). Figure 2 is a scanning electron microscope photograph of Example 1; wherein Figure 2 (b) Yes Figure 2 (a) shows that the obtained ZSM-22-S zeolite has a wheat ear shape, and one end of the nanorod is formed by the accumulation of finer nanofiber bundles. The diameter of the nanofiber bundle is 50-70nm, and the fiber bundle is formed by nanoparticles arranged along the axial direction. Figure 4 This is the N2-adsorption isotherm diagram and pore size distribution curve diagram of the ZSM-22-S zeolite prepared in Example 1.
[0030] Embodiment 2:
[0031] 1.0g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 5.8g 1,6-hexanediamine structure directing agent was added to 19.2g distilled water, and after it was completely dissolved, 0.21g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, and the system became viscous, and finally 22.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3:9K2O:2500H2O:110SiO2:0.8Ni 2+ :50DHA. Finally, the kettle was loaded and statically crystallized at high temperature at 180°C for 36 hours. After the crystallization was completed, the nickel-doped ZSM-22 zeolite with wheat ear morphology was obtained after washing, filtering, drying and high-temperature calcination. The framework silicon-aluminum (Si / Al) ratio of the zeolite is 45, the theoretical loading of Ni in the zeolite is 0.77%, and the actual mass fraction is 0.5%. (The actual loading of nickel is obtained by characterizing the catalyst by X-ray fluorescence spectroscopy or atomic emission spectrometer).
[0032] Embodiment 3:
[0033] 1.1g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 5.2g 1,6-hexanediamine structure directing agent was added to 25.4g distilled water, and after it was completely dissolved, 0.39g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, and the system became viscous, and finally 26.0g silica sol was added, and the silica-alumina gel was formed by vigorous stirring, and the gel composition was: Al2O3:10K2O:3000H2O:130SiO2:1.5Ni 2+ :45DHA. Finally, the kettle was loaded and statically crystallized at high temperature at 170°C for 48 hours. After the crystallization was completed, the nickel-doped ZSM-22 zeolite with wheat ear morphology was obtained after washing, filtering, drying and high-temperature calcination. The framework silicon-aluminum ratio (Si / Al) of the zeolite is 50, the theoretical loading of Ni in the zeolite is 1.5%, and the actual mass fraction is 0.8%. (The actual loading of nickel is obtained by characterizing the catalyst by X-ray fluorescence spectroscopy or atomic emission spectrometer).
[0034] Comparative Example 1:
[0035] 1.1g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 2.3g 1,6-hexanediamine structure directing agent was added to 25.4g distilled water, and after it was completely dissolved, 0.59g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, and the system became viscous, and finally 26.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3:10K2O:3000H2O:130SiO2:2.3Ni 2+ :20DHA. Finally, the mixture was loaded into the kettle and subjected to high temperature static crystallization at 160°C for 40 hours. After the crystallization was completed, the ZSM-22 zeolite was obtained after washing, filtering, drying and high temperature calcination. Figure 5 This is a scanning electron microscope photo of Comparative Example 1. The synthesized zeolite has a rod-like morphology composed of fiber bundles, and is not a wheat-ear-shaped ZSM-22 zeolite assembled by nano-ions.
[0036] Comparative Example 2:
[0037] 0.56g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 9.3g 1,6-hexanediamine structure directing agent was added to 20.6g distilled water, and after it was completely dissolved, 0.6g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, and the system became viscous, and finally 20.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3:5K2O:2500H2O:100SiO2:2.3Ni 2+ :80DHA. Finally, the mixture was loaded into an autoclave and subjected to high temperature static crystallization at a temperature of 160°C for 48 hours. After the crystallization was completed, the zeolite was obtained after washing, filtering, drying and high temperature calcination. Figure 6 This is the X-ray powder diffraction pattern of Comparative Example 2. As can be seen from the figure, in addition to the obvious characteristic diffraction peaks of ZSM-22 zeolite, diffraction peaks of ZSM-5 zeolite appear at diffraction angles of 8.7°, 13.8°, 14.7°, 15.8°, 17.7° and 23.0°, indicating that the synthesized zeolite is a zeolite in which ZSM-22 and ZSM-5 coexist. This shows that increasing the content of DHA in the gel system will promote the formation of ZSM-5 zeolite grains.
[0038] Comparative Example 3:
[0039] 0.56g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and the potassium hydroxide solution was added to the aluminum sulfate solution to obtain solution A; then 7.0g 1,6-hexanediamine structure directing agent was added to 20.6g distilled water, and after it was completely dissolved, 0.6g nickel acetylacetonate was added, and the solution was clarified by stirring to obtain solution B; solution B was slowly added dropwise to solution A, the system became viscous, and finally 20.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3:5K2O:2500H2O:100SiO2:2.3Ni 2+ :60DHA. Finally, the mixture was loaded into the kettle and subjected to high temperature dynamic crystallization at a temperature of 160°C for 48 hours. After the crystallization was completed, the zeolite was obtained after washing, filtering, drying and high temperature calcination.
[0040] Figure 7 This is the X-ray powder diffraction pattern of Comparative Example 3. Figure 7 It can be seen that in addition to the obvious characteristic diffraction peaks of ZSM-22 zeolite, diffraction peaks of ZSM-5 zeolite also appear at diffraction angles of 8.7°, 13.8°, 14.7°, 15.8°, 17.7° and 23.0°, indicating that the synthesized zeolite is a coexistence of ZSM-22 and ZSM-5 zeolite. Figure 8 This is a scanning electron microscope photo of Comparative Example 3, Figure 8 The larger prismatic particles are the heterophase ZSM-5 zeolite.
[0041] Comparative Example 4:
[0042] 0.56g potassium hydroxide was dissolved in 5.0g distilled water to obtain potassium hydroxide solution; 0.67g aluminum sulfate 18hydrate was dissolved in 5.0g distilled water to obtain aluminum sulfate solution, and potassium hydroxide solution was added to aluminum sulfate solution to obtain solution A; then 7.0g 1,6-hexanediamine structure directing agent was added to 20.6g distilled water, and after it was completely dissolved, it was stirred and clarified to obtain solution B; solution B was slowly added dropwise to solution A, and the system became viscous, and finally 20.0g silica sol was added and stirred vigorously to form silica-alumina gel, and the gel composition was: Al2O3: 5K2O: 2500H2O: 100SiO2: 60DHA. Finally, the kettle was loaded and statically crystallized at high temperature, the crystallization temperature was 160°C, and the time was 48 hours. After the crystallization was completed, after washing, filtering, drying and high-temperature calcination, a ZSM-22 zeolite with a wheat ear morphology was obtained. The texture parameter properties of comparative example 4 are shown in Table 1. As can be seen from Table 1, the surface area of Comparative Example 4 (80m 2 / g) and mesopore volume (0.12 cm 3 / g) are lower than the surface area of Example 1 (116m 2 / g) and mesopore volume (0.20 cm3 / g), which shows that the addition of nickel acetylacetonate is beneficial to the synthesis of zeolite to improve the surface area and mesopore volume of the synthetic zeolite. This is because nickel acetylacetonate is easily dissolved in the aqueous solution of 1,6-hexanediamine and interacts with 1,6-hexanediamine, affecting the induced nucleation of 1,6-hexanediamine, causing the morphology of the zeolite to be changed to a certain extent during the nucleation and growth process of the zeolite. Fig. 9 The SEM electron microscopy also shows that in the gel system without the addition of nickel acetylacetonate, the synthesized zeolite is a nanobundle assembled by nanowires.
[0043] Comparative Example 5: Traditional ZSM-22 Synthesis Method
[0044] 0.67g aluminum sulfate 18hydrate and 1.1.85g potassium hydroxide were dissolved in 67.2g distilled water in a beaker. After stirring at room temperature for 30 minutes, 4.1g 1,6-hexanediamine structure directing agent was slowly added to the mixed solution, and then 21.8g silica sol was added under vigorous stirring. The mixture was then stirred at room temperature for 20 minutes to form a silica-alumina gel. The gel composition was: Al2O3: 16.5K2O: 4600H2O: 109SiO2: 35DHA. Finally, the kettle was loaded and high-temperature dynamic crystallization was carried out at a crystallization temperature of 160°C for 48 hours. After the crystallization was completed, after washing, filtering, drying and high-temperature calcination, the traditional needle-shaped ZSM-22 zeolite was obtained, marked as ZSM-22-C.
[0045] Comparative Example 6: Method for synthesizing conventional ZSM-22 doped with metallic nickel
[0046] 0.67 g of aluminum sulfate 18hydrate and 1.85 g of potassium hydroxide were dissolved in 67.2 g of distilled water in a beaker. After stirring at room temperature for 30 minutes, 4.1 g of 1,6-hexanediamine structure directing agent was slowly added to the mixed solution, and then 0.6 g of nickel acetylacetonate was added. 21.8 g of silica sol was added under vigorous stirring, and then the mixture was stirred at room temperature for 20 minutes to form a silica-alumina gel. The gel composition was: Al2O3:16.5K2O:4600H2O:109SiO2:2.3Ni 2+ :35DHA. Finally, the reactor was loaded and high-temperature dynamic crystallization was carried out at a temperature of 160°C for 48 hours. After the crystallization was completed, the traditional needle-shaped ZSM-22 zeolite was obtained after washing, filtering, drying and high-temperature calcination, marked as ZSM-22-C. The silicon-aluminum ratio of the zeolite was 60, and the mass fraction of Ni in the zeolite was 1.5%. (The actual loading amount of nickel was obtained according to the X-ray fluorescence spectrometry analysis or atomic emission spectrometer characterization of the catalyst).
[0047] Catalyst activity evaluation:
[0048] (1) The hydrodeoxygenation reaction of hexadecanoic acid was carried out in a 300 mL parr kettle. The catalyst was reduced before the reaction. The reduction procedure was as follows: the catalyst was heated from room temperature to 550°C at 2°C / min and maintained for 2 h, with a H2 flow rate of 100 mL / min. After cooling to room temperature, the catalyst was poured into a reactor containing the reaction liquid in a hydrogen atmosphere. The reaction conditions were: reaction temperature 260°C, reaction pressure 4.0 MPa, 0.5 g hexadecanoic acid, 0.5 g catalyst of Example 1, 100 mL decahydronaphthalene, rotation speed 500 rpm, and reaction time 4 h. The reaction liquid was analyzed by gas chromatography. The activity data are shown in Table 2.
[0049] (2) According to the above reaction conditions, the deoxidation performance was evaluated on the catalysts of Comparative Example 1, Comparative Example 2 and Comparative Example 3. The activity data are shown in Table 2.
[0050] (3) The zeolite of Comparative Example 4 and Comparative Example 5 was used as a carrier and loaded with 1 wt.% Ni catalyst. The catalyst preparation process was as follows: Weigh the required amount of nickel nitrate hexahydrate (Ni loading in the catalyst was 1 wt.%), dissolve it in distilled water in a centrifuge tube to obtain solution A, wait for it to be completely dissolved until transparent, and add solution A dropwise to the carrier. After impregnation, the sample was placed in an air atmosphere for 10 hours, then dried at 100°C for 10 hours, and finally calcined at 450°C in an air atmosphere for 3 hours. The obtained catalysts were marked as Ni / Comparative Example 4 and Ni / Comparative Example 5, and then the catalysts were reduced: the catalyst was raised from room temperature to 550°C at 2°C / min and maintained for 2h, with a H2 flow rate of 100mL / min. After cooling to room temperature, the catalyst was poured into a reactor containing the reaction solution in a hydrogen atmosphere. The obtained catalyst was evaluated for activity according to the above reaction conditions. The activity data are shown in Table 2.
[0051] Table 1 Texture property parameters of samples
[0052]
[0053] Table 2 Deoxygenation performance of catalysts for hydrodeoxygenation of hexadecanoic acid
[0054]
Claims
1. A method for synthesizing wheat-ear-shaped nickel-doped ZSM-22 zeolite assembled from nanoparticles, characterized in that: Potassium hydroxide solution is added to aluminum sulfate solution to obtain solution A; then 1,6-hexanediamine is added to water, and after it is completely dissolved, nickel acetylacetonate is added, and the solution is clarified by stirring to obtain solution B; solution B is added dropwise to solution A, and the system becomes viscous, and finally silica sol is added and stirred to form silica-alumina gel, and finally the solution is loaded into a kettle and statically crystallized at high temperature. After the crystallization is completed, the solution is washed, filtered, dried and calcined at high temperature to obtain a nickel-doped wheat ear morphology ZSM-22 zeolite, which is marked as ZSM-22-S; wherein the molar ratio of each component of the silica-alumina gel is Al2O3: 5~15K2O: 2500~3500 H2O: 100~140 SiO2: 0.02~3 Ni 2+ :45~70 1,6-hexanediamine.
2. The method for synthesizing wheat-ear-shaped nickel-doped ZSM-22 zeolite assembled by nanoparticles according to claim 1, characterized in that: The conditions for high temperature static crystallization are crystallization at 140~180 °C for 12~48 hours.
3. The method for synthesizing wheat-ear-shaped nickel-doped ZSM-22 zeolite assembled by nanoparticles according to claim 1, characterized in that: The molar ratio of each component of silica-alumina gel is Al2O3:5~10K2O: 2500~3000 H2O: 100~130 SiO2:0.38~2.3 Ni 2+ :45~65 1,6-hexanediamine.
4. Use of the method according to any one of claims 1 to 3 to synthesize wheat-ear-shaped nickel-doped ZSM-22 zeolite assembled by nanoparticles, characterized in that: The wheat-ear-shaped nickel-doped ZSM-22 zeolite is used as a catalyst in the hydrodeoxygenation reaction of hexadecanoic acid.
Citation Information
Patent Citations
A method for synthesizing nano-ZSM-22 zeolite assemblies containing mesoporous structures
CN108529647B
Synthetic method of nano ZSM-22 zeolite assembly containing mesoporous structure
CN108529647A
Hydroisomerization catalyst having nano ZSM-22 zeolite loaded with phosphorus and nickel as well as preparation method and application of hydroisomerization catalyst
CN111013643A